Association between overtime and depressive symptoms among Chinese employees - Liang, Yinyin; Li, Zixuan; Wang, Xinrou; Liu, Pengcheng; Ma, Liang; Wang, Xiaojie (Frontiers in Public Health, 2023)
This study examines the correlation between overtime and depressive symptoms, and analyzed the moderating effect of age, education level, and income level on their correlation by using a nationally representative sample from the Chinese Family Panel Studies (CFPS) in 2018.Participants are divided into three groups: 30-44h/week, 44.1-61.9h/week (defined as overtime group), and ≥62h/week (heavy overtime group). The multiple ordered logistic regression models are conducted to estimate the association between overtime and depressive symptoms. The interaction term of overtime and moderators including age, education level, and income level are introduced into the models to test the moderating effect.The overtime group have an increased probability of depressive symptoms (OR=1.11, 95% CI 1.04-1.20) compared with those who reported working hours 30-44h/week, after controlling for important confounders. What's more, the worsening of depressive symptoms is more pronounced in the heavy overtime group (OR= 1.32,). The moderating effect results show that younger employees, employees with high education levels, and those with high income level are more likely to be affected by the negative effects of overtime.